Surgical Management of Complex Middle Cerebral Artery Aneurysms: An Institutional Review - Bhide, Anuj Arun (Asian J Neurosurg, 2020)
BACKGROUND: Complex middle cerebral artery (MCA) aneurysms are defined as large (≥10 mm) or giant (≥25 mm) aneurysms with M2 branches arising from the aneurysm rather than M1 segments and usually require some form of reconstruction of the bifurcation. Their management is difficult and surgery is preferred over endovascular modalities because of their peculiar angioarchitecture and association with critical branch points or perforators. OBJECTIVES: The study was aimed at analyzing surgically managed complex MCA aneurysms and discussing characteristics not favorable for endovascular management, surgical nuances and clipping strategies, patient outcomes, and newer diagnostic modalities which help improve management. METHODS: Nine cases of surgically operated complex MCA aneurysms were identified from January 2017 to July 2019. The aneurysm characteristics, surgical nuances, clipping strategies, patient outcomes and points not favoring endovascular management were tabulated and analyzed. RESULTS: The mean maximum aneurysm diameter was 13.4 mm and the mean fundus/neck ratio was 1.6. The average microscope time was 124 min, and the most common method was clip reconstruction. The average number of clips used was 2.7 and the mean follow-up was 13 months. All patients have good postoperative outcome (Modified Rankin Score 0-2). The complete occlusion rate was 88.9% with one intraoperative voluntary residual sac which was coated. Computational fluid dynamic study results done preoperatively correlated with intraoperative findings. CONCLUSIONS: MCA aneurysms pose a significant challenge for endovascular treatment because of various factors such as luminal thrombi, complex angio-architecture, precarious branch/perforator locations, broad necks, and fusiform characteristics. Surgical management in experienced hands can tackle all these problems with an armamentarium of clipping techniques and bypass procedures.